Measurement-device-independent multi-party quantum key agreement - Liu, Bing-Xin; Huang, Rui-Chen; Yang, Yu-Guang; Xu, Guang-Bao (Frontiers in Quantum Science and Technology, 2023)
Quantum key agreement (QKA) is an important quantum cryptography primitive. In a QKA protocol, two or more untrusted parties can agree on an identical key in such a way that they equally influence the key and no subset can decide it alone. However, in practical QKA, the imperfections of the participant’s detectors can be exploited to compromise the security and fairness of QKA. To remove all the detector-side-channel loopholes, a measurement-device-independent multi-party QKA protocol is proposed. The protocol exploits the post-selected GHZ states to generate a secure agreement key between these participants, while ensuring the fairness of key agreement. Our protocol provides a new clue for the design of practical QKA protocols.